Subcutaneous Granulomatous Inflammation due to Basidiobolomycosis: Case Reports of 3 Patients in Buruli Ulcer Endemic Areas in Benin - Luc V. C. Brun; Jean Jacques Roux; Ghislain E. Sopoh; Julia Aguiar; Miriam Eddyani; Wayne M. Meyers; Dirk Stubbe; Marie T. Akele Akpo; Françoise Portaels; Bouke C. de Jong (Case Reports in Pathology)
Background. Basidiobolomycosis is a rare subcutaneous mycosis, which can be mistaken for several other diseases, such as soft tissue tumors, lymphoma, or Buruli ulcer in the preulcerative stage. Microbiological confirmation by PCR for Basidiobolus ranarum and culture yield the most specific diagnosis, yet they are not widely available in endemic areas and with varying sensitivity. A combination of histopathological findings, namely, granulomatous inflammation with giant cells, septate hyphal fragments, and the Splendore-Hoeppli phenomenon, can confirm basidiobolomycosis in patients presenting with painless, hard induration of soft tissue. Case Presentations. We report on three patients misdiagnosed as suffering from Buruli ulcer, who did not respond to Buruli treatment. Histopathological review of the tissue sections from these patients suggests basidiobolomycosis. All patients had been lost to follow-up, and none received antifungal therapy. On visiting the patients at their homes, two were reported to have died of unknown causes. The third patient was found alive and well and had experienced local spontaneous healing. Conclusion. Basidiobolomycosis is a rare subcutaneous fungal disease mimicking preulcerative Buruli ulcer. We stress the importance of the early recognition by clinicians and pathologists of this treatable disease, so patients can timely receive antifungal therapy.